Pastors in the classics : timeless lessons on life and ministry from world literature - Ryken, Leland; Ryken, Philip Graham, 1966-; Wilson, Todd A., 1976- (Grand Rapids, MI : Baker Books, 2012)
"Throughout the history of English literature, clergy have figured prominently in novels, plays, morality tales, and even poetry. Pastors in the Classics is a unique exploration of literary masterpieces in which the pastor's experience is a major part of the story. This collection uncovers the good, the bad, and the ugly ways in which pastors have been presented to the reading public for the past half millennium, and how pastors today can glean wisdom from those who have gone before. Whether you are a pastor or a lover of great literature, you will find insight, humor, and grace within these pages."--Back cover.
The Dean's Watch -- Death comes for the archbishop -- Death in holy orders -- Deep river -- Father Brown -- The flight of Peter Fromm -- The gauntlet -- Godric -- The God-seeker -- Go tell it on the mountain -- Holy masquerade -- In My father's house -- In the beauty of the Lilies -- The Ionian mission -- Jane Eyre -- Jonah's gourd vine -- Les t
Includes bibliographical references.
Keywords: Clergy in literature